If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(6x-2)+72+(11x-9)=180
We move all terms to the left:
(6x-2)+72+(11x-9)-(180)=0
We add all the numbers together, and all the variables
(6x-2)+(11x-9)-108=0
We get rid of parentheses
6x+11x-2-9-108=0
We add all the numbers together, and all the variables
17x-119=0
We move all terms containing x to the left, all other terms to the right
17x=119
x=119/17
x=7
| 90=30-7r | | 2x(2x+3x)-3x=14 | | z-235=176 | | -8x+5+2x=-13 | | 3y-47=y+27 | | 2x+13-3x=x+5 | | 10r+8=18 | | 27=x(5)-x(2) | | x+19=-x-17 | | -10x+6=10-4x | | -9x+7+10x=24 | | 12(4x-1)=372 | | -4(10n-6)=-406 | | 45x+67=45x+78 | | 11=u/27 | | 9=30-7r | | 5m+2=-3m-6 | | 2(4x+13)=130 | | 5m+2=–3m–6 | | 6x+3=3-6x | | 880=-22q | | 7+4=-4r+6+4r-1 | | 0=224t-16t2 | | 112=19x | | 5a+3(a+3)-a=a | | k/4=25 | | (4x)=24 | | 95=-8x=14 | | 5m=–45 | | 1.2x^2-0.7x-22.4=0 | | 3^(x-3)=15 | | (5x)=120 |